The recruitment and retention of speech and language therapists: What do university students find important? - Whitehouse, A.; Hird, Kathryn; Cocks, Naomi (Association of Schools of Allied Health Professions, 2007)
Education of health professionals is costly to the general community and more specifically the educational sector. The increasing need for speech and language therapy (SLT) services, coupled with poor employment retention rates, poses serious cost-benefit considerations. The poor job retention rates among speech and language therapists are associated with high levels of job dissatisfaction. One factor known to influence job satisfaction is the congruence between one's career motivation and actual career experience. The current study sought to explore (1) why students choose to embark on an SLT degree, (2) what factors are important to maintain their long-term employment in SLT, and (3) how long they predicted they would remain in the workforce practicing in SLT. Students from two tertiary SLT courses, one in Australia (n=67) and one in the United Kingdom (n=84), completed an online questionnaire targeting these issues. Students' responses were consistent across cohorts, so they were combined into one data set. Three categories of responses emerged, relating to altruism (i.e., helping others), intellectual interest (i.e., interested in disease and disability), and professional issues (e.g., salary, desire for a professional career).There was good agreement in responses to questions focusing on why participants chose to study SLT and what they foresaw as important for their future career. Students who were motivated to enter SLT for professional reasons tended to report that they would remain in the profession for a shorter time than those students who chose the career with a primarily humanistic or intellectual motivation. The implications of these findings for educators and professional bodies are discussed.